Planning and control of a hybrid vacuum-forming system based on screw-pin tooling - Wang, Zhijiang; Wang, Yan; Gindy, Nabil (World Scientific and Engineering Academy and Society, 2010)
This paper introduced planning and control of a hybrid vacuum-forming machine system (HAVES). The HAVES was developed to integrate CAD/CAM, screw-pin tooling, CNC, vacuum forming and optical measurement device together to produce vacuum forming components. The screw-pin tooling was employed to replace traditional dedicated solid tooling and its reconfigurability provided the HAVES with advantages in rapid producing small batch and mass customization products. The whole control system of the HAVES is divided into two parts: one for screw-pin tooling adjustment and machining by using CNC control, and the other for vacuum forming by using PLC control. The detail design of the control system was discussed.